Analisis Peranan Pajak Hotel dan Pajak Restoran terhadap Pendapatan Asli Daerah di Kota Banjarmasin - Subhannor, Haris Novitri (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The research method used is a quantitative descriptive analysis by usingsecondary and primary data, through the collection of information and data availableat the Regional Financial Agency of Banjarmasin City and related agencies, as wellas the literature that is related to this research and conduct interviews or directinterviews with relevant agencies. Based on the above calculation, the efforts thatmust be done by the Regional Government, especially the Regional Finance Agency ofBanjarmasin City are among others: multiplying the event about taxes that appeal tothe public, increasing the socialization of the importance of paying taxes, providingtransparency about tax income, increasing attractiveness tourism to be able to stealvisitors to the hotel as well as kerestoran, and provide easy access from theprocedures of registering or paying taxes.